Pengembangan Modul Pembelajaran Berbasis Problem Based Learning dalam Kurikulum Merdeka Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa - Hulu, Friska Putri Magdalena; Mendrofa, Ratna Natalia; Mendrofa, Netti Kariani; Telaumbanua, Yakin Niat (Pusat Studi Bahasa dan Publikasi Ilmiah, 2025)
Initial observations at SMP Negeri 3 Alasa Talumuzoi revealed that students’ critical thinking skills were very low, and the available teaching materials were limited and highly dependent on the teacher. To address these issues, this study aimed to develop a problem-based learning (PBL) module that is valid, practical, and effective in improving students’ critical thinking skills. The research employed a development design using the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. Data collection instruments comprised learning outcome tests, validation questionnaires from material, language, and design experts, as well as teacher and student response questionnaires. Both quantitative and qualitative data were analyzed: quantitative data included validator scores, student and teacher responses, and learning outcomes, while qualitative data consisted of comments and suggestions on the developed module. The results demonstrated that the PBL module met validity criteria for content, language, and design. It was highly practical, with a student practicality score of 96% and a teacher practicality score of 92.8%. Furthermore, the module effectively improved students’ critical thinking skills, achieving an average score of 80.20%, categorized as very high, and a classical mastery percentage of 91.66%, categorized as very effective. In conclusion, the developed problem-based learning module fulfilled the research objectives and provides a reliable, practical, and effective tool for enhancing students’ critical thinking skills in mathematics.